Hybrid Learning of Daviq.com in the Subject of Teaching Listening and Speaking - Rizal, Daviq (Vision: Journal for Language and Foreign Language Learning, 2017)
The term hybrid learning was used to describe online learning combined with face-to-face interaction in the classroom. There are two research questions the first question is how the development of hybrid learning in http://daviqr.com/ is. The second one is how the moodle-based hybrid learning of http://daviqr.com/ as a teaching model in the subject of teaching listening and speaking to the students of English Department of IAIN Walisongo Semarang in the academic year of 2013/2014 is. This research is a research and development, which has the population of all fourth semester English department students of the Faculty of Teachers' Training and Education, IAIN Walisongo Semarang that takes the subject of Teaching Listening and Speaking in the academic year 2013/2014, which consists of three classes. The number of population is 120 students. Regarding the research findings that there are some main reasons why most students agree that the hybrid learning course is an exciting course and why they prefer the hybrid online course or the combination between online and traditional classroom. First, the course outline and objectives were made clear. Second, they learned a lot from this hybrid course. Third, the reading materials were clear and informative. Fourth, the level of this hybrid course is just right. Fifth, the total study load of this hybrid course is in proportion to the number of semester credits is just right. Sixth, the amount of their interaction with other students is a little better. Seventh, the quality of their interaction with other students is a little better. Eighth, the amount of their interaction with the instructor is a little better. Ninth, the quality of their interaction with the instructor is a little better and about the same. Tenth, compared to a face-to-face (traditional) class of equal credits, the workload of this online course is somewhat more. There are some recommendations I should give. First, UIN Walisongo Semarang must design e-learning for lecturers as many students like hybrid courses. Second, the faculty must improve the quality of Wi-Fi hotspots.